Dynamics of multilevel governance in racial equality policies in Brazil : an analysis of national and local instruments - Sena Silva, Lucas; Dias Teixeira, Graziela (Revista do Serviço Público, 2025)
In this paper, we examine the dynamics of multilevel governance in racial equality policies in Brazil, comparing the national and local levels, specifically the federal government and the municipality of São Paulo. In addition to the theoretical elements that frame the discussion of federalism, we analyze the legal, organizational, and budgetary contexts inherent to the issue. Accordingly, we seek to answer the following questions: How is the governance of public policies on racial equality influenced by political and institutional factors? Has there been continuity in these policies at the local level, despite signs of dismantling at the national level? We adopt a mixed-methods approach, focusing on the period from 2019 to 2022. In our concluding remarks, we emphasize the need to expand studies that observe and compare local and national dynamics, while considering the impacts of policy dismantling and retrenchment. We also note that, although the federal level exhibited signs of dismantling, retrenchment, and discontinuity, the local level in São Paulo, based on budget data and analysis of organizational design, demonstrated continuity in racial equality policy, at least in terms of institutional instruments.